Assessing the security implications of the ECOWAS protocol on free movement in Nigeria - Ochoga, Ochoga Edwin; Osimen, Goddy Uwa; Pokubo, Ibiso Esther (International Journal of Innovative Research and Scientific Studies, 2025)
The study is designed to assess whether the ECOWAS Protocol on Free Movement of Persons has had negative implications for Nigeria’s national security. The study used key informant interviews and secondary sources as instruments to collect qualitative and quantitative data. The study critiqued the economic integration theory, and the assumption of the theory is premised on the removal of tariff and non-tariff barriers among member states for the free movement of factors of production across national borders. It used the obtained qualitative and quantitative data to demonstrate how Nigeria’s national security has been negatively affected by the free movement regime of ECOWAS. The study reveals that there is a relationship between the free movement enabled by the Protocol and the spread of Boko Haram terrorism, cattle rustling, armed banditry, and the activities of violent herders in Nigeria. Poor implementation of the Protocol by Nigeria, arising from the non-enforcement of Article 4 of the Protocol, the absence of a migration central database, porous borders, and socio-cultural affinities among border communities, are the challenges associated with the implementation of the Protocol in Nigeria. This study argues that proponents of the ECOWAS Protocol on free movement are mainly concerned about the economic benefits of the Protocol for member states without considering the socio-economic complexities associated with the window provided by the free movement regime occasioned by ECOWAS. It is upon this contextual premise that the study reveals that, unlike previous studies, every region has its own specificities to take into account when addressing the concept of free movement. Indeed, given the specific character of migratory movements in each region, there are perhaps as many different approaches to the subject as there are regions. In conclusion, despite the socio-economic benefits of the free movement regime, it has shown that the Protocol has been poorly implemented by Nigeria, with its attendant consequences on Nigeria’s national security. This finding was arrived at by subjecting the conventional perspective of regional economic integration to scrutiny, using Nigeria as a case study. The study recommends that guided economic integration is more desirable for Nigeria’s national security than the ideological allegory of the economic integration theory.